Optimizing time and power allocation for cooperation diversity in a decode-and-forward three-node relay channel - Elsheikh, Elsheikh Mohamed Ahmed (Academy Publisher, 2008)
Providing space diversity at mobile devices such as handsets, personal digital assistants (PDA), etc is costly and problematic, due to their strict space limitation. Recent studies, however, have revealed that extraordinary diversity gain, which results in the remarkable benefits of an increased achievable transmission code-rate and a reduced information outage probability, can be obtained from a relay node in the proximity, which forwards the decoded information from the source node to the intended destination node via a diversity path. While previous works had shown the impressive gains from simple fixed-relaying schemes over non-relaying, this paper takes an information-theoretic viewpoint to study the optimal decode-and-forward (DF) single-hop relay strategy for maximizing the mutual information between the source and destination nodes exploiting the instantaneous channel state information at the nodes (CSIN), and for minimizing the outage probability if only the statistical channel information is known at the nodes (SCIN). In particular, our aim is to optimize the time and power distribution between the direct transmission and relaying phases, for a cooperative three-node relay fading channel.